Pengembangan Bahan Ajar Tematik Digital untuk Siswa Kelas V Sekolah Dasar - Dina Yuli Agustin; Punaji Setyosari; Suharti Suharti (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The development of digital thematic teaching materials aims to produce a product that is feasible, practical to use, effective for improving the quality of learning, and interesting for students to learn. The results of the development showed a positive impact from the use of the product with an increase in learning activities of 92.14% with the criteria of